Cannabinoid receptor expression in the bladder is altered in detrusor overactivity. Issue 1 (January 2016) - Bakali, Evangelia; McDonald, John; Elliott, Ruth; Lambert, David; Tincello, Douglas
Abstract Introduction Immunohistochemical (IHC) evidence shows that cannabinoid receptors (CB) are expressed in human bladders and cannabinoid agonists are known to inhibit detrusor contractility. However, the mechanism for this inhibition remains unknown. In addition, the role of CB in detrusor overactivity (DO) is under-investigated. The aim of this study was to compare CB expression in normal and DO human bladders and to further characterise these receptors. Methods Polymer chain reaction (PCR) was used to detect differences in CB transcripts in bladder samples. Differences in CB protein expression was assessed by IHC. Immunofluorescence (IF) was used to evaluate co-localisation of CB with nerve fibres. Receptor density and binding affinity were measured using the cannabinoid radioligand [3 H]-CP-55, 940. Results There were higher levels of CB1 transcripts in the urothelium of patients with DO and lower levels in the detrusor, compared with normal bladders. Radioligand binding revealed CB density of 421 ± 104 fmol/mg protein in normal human bladders. IHC confirmed these findings at the protein level. IF staining demonstrated co-localisation of CB1 with choline acetyltransferase-(ChAT)-positive nerves in the detrusor and co-localisation with PGP9.5 in both urothelium and detrusor. CB2 was co-localised with both ChAT and PGP9.5 in the urothelium and the detrusor. Conclusions Cannabinoid receptor expression is reduced in the detrusor of patients with DO, which may play a role in the pathophysiology of the disease. Co-localisation of CB receptors with cholinergic nerves may suggest that CB1, being localised on pre- and postsynaptic terminals, could influence neurotransmitter release. Our findings suggest the potential role of cannabinoid agonists in overactive bladder pharmacotherapy.